(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The problem of analyzing crime has become crucial to law enforcement agencies because of growing urbanization, advanced criminal activities, and the weaknesses of the conventional manualized approaches. Traditional methods are likely to fail when dealing with large volumes of data, slow reaction time, and offensive patterns or risky spots. This paper intends to test and build intelligent crime pattern and hotspots analysis system to facilitate proactive policing and decision-making based on data. The proposed system is an approach based on simulation that involves the integration of machine-learning algorithms and spatial analysis as ways of identifying, classifying, and visualizing crime patterns. The artificial data sets were created to imitate a real-life crime situation and controlled experimentation was possible. The main methods used are clustering which detects patterns (K-Means and DBSCAN), classification models (Random Forest, which predicts types of crime) and Kernel Density Estimation (KDE) (identifies hotspots). The results of the study proved that the system was effectively used to group crime incidences into significant clusters, detect high-density crime localities and offer predictive data that are highly accurate, precise, and recall. Spatial visualizations and heat maps were used to identify the common hotspots of crime, allowing resources to be focused. Conclusively, the smart system is enhanced when compared to the general crime analysis systems since it improves efficiency, accuracy, and actionable data to law enforcement agencies. Combining machine learning and spatial analytics gives it a scalable, data-driven platform that can be used to support proactive policing, optimized resource allocation, and more effective crime prevention strategies, which lead to better community safety.